Corticospinal excitability following repetitive voluntary movement. (November 2018) - Ishikawa, Natsumi; Miyao, Ryunosuke; Tsuiki, Shota; Sasaki, Ryoki; Miyaguchi, Shota; Onishi, Hideaki
Highlights: The simple rhythmic task transiently reduced MEP amplitudes. The visuomotor task increased MEP amplitudes. No MEP changes were observed following the adjustment task and the simple isometric task. This study suggests that PED is induced by simple rhythmic movement. Abstract: Post-exercise cortical depression (PED) is induced by non-fatiguing finger movement. Because the type of exercise that causes PED remains unclear, we conducted two experiments to clarify which exercise factors induce PED. Fifteen healthy participants performed repetitive abduction movements of the right index finger at 2.0 Hz (simple rhythmic task) and 0.2 Hz (adjustment task) for 6 min each in experiment 1. Twelve healthy participants performed repetitive and isometric abduction contractions of the right index finger at 1.0 Hz with visuomotor tracking (visuomotor task) and without visuomotor tracking (simple isometric task) for 5 min each in experiment 2. Muscle contraction levels were 10% of the maximum voluntary contraction in all tasks. Motor evoked potentials (MEPs) evoked by transcranial magnetic stimulation were recorded from the right first dorsal interosseous muscle before and after the movement tasks. The simple rhythmic task transiently reduced MEP amplitudes when compared with baseline in experiment 1. In contrast, the visuomotor task increased MEP amplitudes in experiment 2. No MEP changes were observed following the adjustment task in experiment 1 and the simple isometric task in experiment 2. This study suggests that PED is induced by simple rhythmic movement.